By more than providence : grand strategy and American power in the Asia Pacific since 1783 - Green, Michael J. (Nancy Bernkopf Tucker and Warren I. Cohen books on American-East Asian relations., 2017)
"Soon after the American Revolution, certain of the founders began to recognize the strategic significance of Asia and the Pacific and the vast material and cultural resources at stake there. Over the coming generations, the United States continued to ask how best to expand trade with the region and whether to partner with China, at the center of the continent, or Japan, looking toward the Pacific. Where should the United States draw its defensive line, and how should it export democratic principles? In a history that spans the eighteenth century to the present, Michael J. Green follows the development of U.S. strategic thinking toward East Asia, identifying recurring themes in American statecraft that reflect the nation's political philosophy and material realities. Drawing on archives, interviews, and his own experience in the Pentagon and White House, Green finds one overarching concern driving U.S. policy toward East Asia: a fear that a rival power might use the Pacific to isolate and threaten the United States and prevent the ocean from becoming a conduit for the westward free flow of trade, values, and forward defense. 'By More Than Providence' works through these problems from the perspective of history's major strategists and statesmen, from Thomas Jefferson to Alfred Thayer Mahan and Henry Kissinger. It records the fate of their ideas as they collided with the realities of the Far East and adds clarity to America's stakes in the region, especially when compared with those of Europe and the Middle East."--JSTOR website (viewed February 24, 2017)